PRESENT AND FUTURE OF GOVERNMENTAL ACCOUNTING. - Chatters, Carl H. (The Accounting Review, 1939)
Abstract The article focuses on the progress made in the U.S. governmental accounting and the future prospects related to the subject. The Federal government's accounting for general funds has reached a standstill because the Comptroller-General's office has been more interested in rejecting minor expenditures than in setting up a modern and complete accounting plan for the entire Federal establishment. Local governments have improved their general accounting, budgetary accounting, and utility accounting and have just begun to enter the field of cost accounting. The rapid development of governmental accounting awaited the establishment of recognized standards. Standards, principles, and recognized procedures have now been developed on a much broader scale through the work of the National Committee on Municipal Accounting, the Municipal Finance Officers' Association, the American Institute of Accountants, the American Accounting Association, and other allied groups. At present the general accounting procedure of the Federal government is utterly inadequate to present factual information about assets and liabilities. Governmental accounting has reached its best development in cities over 10,000 population. The counties have been much slower to adopt improved procedures because county finance officials are usually elective; because the county government lacks coordination; and because the term of office of county officials is shorter than the term of city officials.